2018
DOI: 10.1210/en.2018-00109
|View full text |Cite
|
Sign up to set email alerts
|

Eldecalcitol Causes FGF23 Resistance for Pi Reabsorption and Improves Rachitic Bone Phenotypes in the Male Hyp Mouse

Abstract: X-linked hypophosphatemia (XLH), the most common form of inheritable rickets, is caused by inactivation of phosphate-regulating gene with homologies to endopeptidases on the X chromosome (PHEX) and leads to fibroblast growth factor (FGF) 23-dependent renal inorganic phosphate (Pi) wasting. In the present study, we investigated whether maintaining Pi homeostasis with a potent vitamin D3 analog, eldecalcitol [1α,25-dihydroxy-2β-(3-hydroxypropyloxy) vitamin D3; ED71], could improve hypophosphatemic rickets in a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 53 publications
0
29
0
Order By: Relevance
“…Despite an increase in bone mass, Scl‐Ab treatment did not improve femoral length or body weight in Hyp animals. However, other studies have found that calcitriol is capable of normalizing body weight and femur length in Hyp mice . Therefore, it is possible that combining calcitriol with Scl‐Ab treatment, as has been done in Scl‐Ab clinical trials for osteoporosis, could potentially improve growth in XLH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite an increase in bone mass, Scl‐Ab treatment did not improve femoral length or body weight in Hyp animals. However, other studies have found that calcitriol is capable of normalizing body weight and femur length in Hyp mice . Therefore, it is possible that combining calcitriol with Scl‐Ab treatment, as has been done in Scl‐Ab clinical trials for osteoporosis, could potentially improve growth in XLH.…”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have found that calcitriol is capable of normalizing body weight and femur length in Hyp mice. (19,20) Therefore, it is possible that combining calcitriol with Scl-Ab treatment, as has been done in Scl-Ab clinical trials for osteoporosis, (8) could potentially improve growth in XLH. Additionally, burosumab, a monoclonal antibody to FGF23 protein, has been reported to increase bone length in Hyp mice (21) and may present another potential option for combinatory therapy with Scl-Ab.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, NaPi2c expression is suppressed in NHERF3-KO mice 33 . We previously reported differences in signals between the phosphaturic action of FGF23 and the inhibitory effect on vitamin D synthesis 34 . Therefore, it is considered that the effect of TRAP deficiency is limited to the control function of NaPi2a.…”
Section: Discussionmentioning
confidence: 99%
“…TRAP is expected to regulate the amount of NaPi2a in response to a Pi deficiency or excess and regulates the responsiveness of phosphaturic hormone. For example, vitamin D treatment in Hyp mice restores serum Pi levels by causing FGF23 resistance to NaPi2a/NHERF1 34,45 . Thus, TRAP, a 12/13/21 strongly correlated molecule with NaPi2a in the GCNs, is thought to be involved in the regulation of NaPi2a by phosphaturic hormones in the kidney and the prevention of hyperphosphatemia in response to a high dietary Pi load (Figure 11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation